Sub-synchronous resonance in wind energy integrated grid – problem and mitigation techniques – a review - Chethan Hiremarali Ramalingegowda; Mageshvaran Rudramoorthy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
When wind energy conversion systems (WECS) are integrated with the Grid system then there are power quality issues arises. The fluctuation in the wind power delivery to the grid demands robust control for a better power quality. Therefore, voltage and frequency stability due to integration of wind to the grid is the primary concern to improve the overall grid integration capability for WECS. This paper reviews the power quality issues in the power grid due to introduction of WECS. The WECS integration with the grid introduces dynamic issues that include sub-synchronous resonance (SSR), low voltage ride through (LVRT), frequency support from wind generation, synchronization, and transients. Also, it focusses on the sub synchronous resonance introduced due to introduction of doubly-fed induction generator (DFIG) wind turbines to the transmission lines with capacitive seriescompensation. The review of various power quality issues and methods used by the researcher’s mitigations are discussed and detailed further research perspective.